Health-related Quality of Life Following Hybrid Minimally Invasive Versus Open Esophagectomy for Patients With Esophageal Cancer, Analysis of a Multicenter, Open-label, Randomized Phase III Controlled Trial: The MIRO Trial. Issue 6 (June 2020) - Mariette, Christophe; Markar, Sheraz; Dabakuyo-Yonli, Tienhan Sandrine; Meunier, Bernard; Pezet, Denis; Collet, Denis; D'Journo, Xavier Benoit; Brigand, Cécile; Perniceni, Thierry; Carrere, Nicolas; Mabrut, Jean Yves; Msika, Simon; et al.
Abstract : Background: Hybrid minimally invasive esophagectomy (HMIE) has been shown to reduce major postoperative complications compared with open esophagectomy (OE) for esophageal cancer. Objectives: The aim of this study was to compare short- and long-term health-related quality of life (HRQOL) following HMIE and OE within a randomized controlled trial. Methods: We performed a multicenter, open-label, randomized controlled trial at 13 study centers between 2009 and 2012. Patients aged 18 to 75 years with resectable cancers of the middle or lower third of the esophagus were randomized to undergo either transthoracic OE or HMIE. Patients were followed-up every 6 months for 3 years postoperatively and global health assessed with EORTC-QLQC30 and esophageal symptoms assessed with EORTC-OES18. Results: The short-term reduction in global HRQOL at 30 days specifically role functioning [−33.33 (HMIE) vs −46.3 (OE); P = 0.0407] and social functioning [−16.88 (HMIE) vs −35.74 (OE); P = 0.0003] was less substantial in the HMIE group. At 2 years, social functioning had improved following HMIE to beyond baseline (+5.37) but remained reduced in the OE group (−8.33) ( P = 0.0303). At 2 years, increases in pain were similarly reduced in the HMIE compared with the OE group [+6.94 (HMIE) vs +14.05 (OE); P = 0.018]. Postoperative complications in multivariate analysis were associated with role functioning, pain, and dysphagia. Conclusions: Esophagectomy has substantial effects upon short-term HRQOL. These effects for some specific parameters are, however, reduced with HMIE, with persistent differences up to 2 years, and maybe mediated by a reduction in postoperative complications. Abstract : Supplemental Digital Content is available in the text